Corporate sustainability priorities, elements and business areas - Jamaluddin, Noor Asma; Mohamed, Rapiah; Muhammad Jamil, Che Zuriana (2015)
Corporate sustainability is one of the vital corporate agenda.Its pragmatic and profound impact on business strategy and operations could lead to achieving competitive advantage in the long run. This paper investigates the sustainability priority, elements and business areas among Malaysian public listed companies.Three sectors of industry namely; consumer, trading and industrial companies were selected and surveyed using mail survey method.Our findings show that majority of the companies put a high priority on sustainability initiatives.However, only a few companies claimed that they have a management council or special committee to manage sustainability efforts.This study also identifies energy usage, water usage, recycling, employee well-being and community involvement as the top five elements of sustainability. As for the business area’s priority in sustainability initiatives, the findings show that operations (processes) and customer use of products were ranked as the highest business areas’ priority, followed by facilities (building), supply chain (supplier product selection), distribution and logistics, product design and end of life product disposal/recovery.These results suggest that corporate leaders are well informed of the sustainability initiatives and opportunities across their entire value chain